AUTOESTIMA Y RENDIMIENTO ESCOLAR DE LOS ALUMNOS DEL TERCER GRADO DE SECUNDARIA DEL COLEGIO ALBERT EINSTEIN, CHINCHA ALTA, 2016 - FERREYRA GUGLIERMINO, ROSANNA CECILIA (2016)
Objective: To determine the relationship between self-esteem and school performance of third grade high school students from Colegio Albert Einstein, chincha alta, 2016 Material and methods: In this study, a basic orientation was proposed in terms of research, since new knowledge will be generated through the relationship between variables. The research level corresponds to the correlational type, because it will seek to quantify the variables and establish relationships between them (Hernández, 2014). Population: The population was made up of 177 third-year (secondary) students from Colegio Albert Einstein, Chincha Alta, who were enrolled in 2016. Through non-probabilistic convenience sampling, a sample of 60 students was obtained who met criteria inclusion and exclusion. Results: In the present work it was found that 65.6% (42) are 14 years old, that 31.3% (20) have 1 brother, 28.1% (18) have more than 3 brothers, that 60.9% (39) live with the complete family, 28.1% (18) live with the mother or father. 64.1% (41) have moderate self-esteem, 20.3% (13) have low self-esteem, 15.6% (10) have high self-esteem. 65.6% (42) have regular school performance, 20.3% (13) have good school performance, 12.5% (8) have poor school performance. there is a significant relationship between students' self-esteem and school performance. Conclusion: If there is a significant relationship between self-esteem and school performance (p = 0.00) of third grade high school students from Colegio Albert Einstein, Chincha Alta, 2016. Keywords: Self-esteem, performance, academic, school, students, educational institution